Approach to self-evaluation of perceived quality in elderly care services - Ernesto José López González; Yolanda Cabrera Macías; José Aurelio Díaz Quiñones; Ernesto López Cabrera; Ana María Gálvez González; Giset Jiménez López (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2019)
Foundation: To evaluate periodically the perceived quality of care services for the elderly is one of the strategic elements on which the transformation of health systems is based in order to achieve efficiency, support decision-making and use resources wisely in the organizations that offer them. Objective: to implement a procedure of self-evaluation of the perceived quality in the services of assistance to the elderly of the nursing home Hermanas Giral, of Cienfuegos. Methods: development research based on a descriptive cross-sectional design, conducted during the month of February 2018 at the Hermanas Giral nursing home in Cienfuegos. Survey, interview and documentary review were used. The following instruments were applied: a questionnaire for the satisfaction of users in nursing homes, a questionnaire for the satisfaction of providers in nursing homes and a form for the nursing home process, previously validated by researchers from the National School of Public Health. Results: users and providers are not satisfied (poor % 80). Conclusions: the self-evaluation of the service perceived quality in general was classified as inadequate.